Rare case of ruptured uterus in previously normal delivered patient due to hydatid cystic disease in pregnant uterus - Bargaje, Ganesh Mahadeo; Ghumare, Jitendra Pundlik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Hydatid cystic disease is parasitic disease caused by Echinococcus granulosus. Dogs and carnivors like fox are definitive hosts harbouring warms in intestine. Eggs passed in stools eaten by intermediate hosts and larvae encyst in liver, lungs and other organs. Humans are accidental hosts. Incidence of hydatid cystic disease in genital organs is low around 0.5%. Hydatid cyst most often found in liver - 60%, lungs - 30% accounting approximately 90% of the disease. Incidence of hydatid disease in pregnancy is very rare ranging from 1/20000 to 1/30000. 22 years old G2P1L1 with 39weeks gestation age (GA) with intrauterine fetal death (IUFD) with query ruptured uterus, extra uterine pregnancy, transverse lie with severe anaemia referred from Jalgaon civil hospital for further management.